Brewing Interdisciplinary Collaboration in Higher Education: The Centro de Enseñanza Técnica y Superior (CETYS) BrewEd Initiative as a Model for Community-Driven Learning - Francisco Alberto Núñez-Tapia; Paulina A. Vargas-Larraguível (Interdisciplinary Journal of Partnership Studies)
The Centro de Enseñanza Técnica y Superior (CETYS) BrewEd Initiative demonstrates the transformative power of interdisciplinary collaboration by merging entrepreneurship education with the Mexicali region’s craft brewing industry. This innovative model transforms local businesses into experiential learning environments, integrating academic theory with hands-on practice. Through co-curricular workshops, industry partnerships, and cultural programs, students gain direct exposure to entrepreneurial challenges while reinforcing community ties and fostering sustainable business practices. Early findings underscore BrewEd’s effectiveness in equipping students with applied business skills, fostering awareness of community-driven economic development, and providing a scalable framework for interdisciplinary education. By blending experiential learning with meaningful industry engagement, BrewEd offers a replicable model for universities aiming to connect education, industry, and cultural heritage—contributing to global conversations on entrepreneurship education, sustainability, and community-driven learning.